An experimental kinetic study and products research of the reactions of O3 with a series of unsaturated alcohols. (November 2016) - Chen, Yi; Wang, Jing; Zhao, Sanping; Tong, Shengrui; Ge, Maofa
Abstract: The gas-phase reactions of unsaturated alcohols with O3 were investigated in FEP Teflon film chamber at 298 K and 760 torr of atmosphere pressure. The rate constants of the reactions of C6-C8 alkenols with O3 were determined using both the absolute and the relative rate method, and the measured values were (5.96 ± 0.35) × 10 −17  cm 3  molecule −1  s −1 for (Z)-3-hexen-1-ol, (5.12 ± 0.30) × 10 −17  cm 3  molecule −1  s −1 for (Z)-3-hepten-1-ol, and (5.66 ± 0.52) × 10 −17  cm 3 molecule −1 s −1 for (Z)-3-octen-1-ol, respectively. The gas-phase products of these reactions mentioned above were detected using proton-transfer-reaction mass spectrum (PTR-MS). HOCH2 CH2 CHO, CH2 CH2 CHO, HCHO and CH3 CHO were identified as the main gas products for (Z)-3-hexen-1-ol. HOCH2 CH2 CHO and CH3 (CH2 )2 CHO dominated the gaseous products for (Z)-3-hepten-1-ol. And for (Z)-3-octen-1-ol, CH3 (CH2 )3 CHO, CH3 (CH2 )2 CHO and HOCH2 CH2 CHO were the main gaseous products. The SOA yields were monitored at the same time, which were 0.184 ± 0.013, 0.213 ± 0.017, 0.232 ± 0.021 for (Z)-3-hexen-1-ol, (Z)-3-hepten-1-ol and (Z)-3-octen-1-ol, respectively. The possible reaction mechanisms were proposed and discussed. The kinetic data presented here has been used to estimate their atmosphere lifetimes and the reaction reactivity. The atmosphere implication of these reactions has also been discussed. Graphical abstract: Highlights: The rate constants of O3 with C7, C8 enols were obtained for the first time. Obtained rate constants were correlated with their EHOMO calculations. The gas-phase products and the SOA yields were detected. The possible reaction mechanisms were proposed. Atmospheric lifetimes of selected unsaturated alcohols were estimated.